Tara Road - Binchy, Maeve (Orion Books Ltd, 1999)
Ria and Marilyn have never met - they live thousands of miles apart, separated by the Atlantic Ocean: one in a big, warm, Victorian house in Tara Road, Dublin, the other in a modern, open-plan house in New England. Two more unlikely friends would be hard to find: Ria's life revolves around her family and friends, while Marilyn's reserve is born of grief. But when each needs a place to escape to, a house exchange seems the ideal solution. Along with the borrowed houses come neighbours and friends, gossip and speculation as Ria and Marilyn swap lives for the summer...
Keywords: Dublin (Ireland)-Female friendship-Romance-Home Exchanging-Fiction